2015 3rd International Renewable and Sustainable Energy Conference (IRSEC) 2015
DOI: 10.1109/irsec.2015.7455081
|View full text |Cite
|
Sign up to set email alerts
|

A gray box modeling of a photovoltaic cell under low illumination in materials handling application

Abstract: This paper presents a gray box model of a photovoltaic (PV) cell working under low illuminance artificial indoor lighting conditions. A mathematical model of PV cells with single and two diode configuration is used. Additionally a platform for the measurement of the PV cells within the indoor environment is presented. An optimization problem is formulated to tune the internal parameters of the mathematical models according to the collected data from measurement platform. Fluorescent and halogen lights are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Simulink Design Optimization Tool (SDO) was used for parameter identification. Masoudinejad et al [63] investigated the use of a serial GB model of a photovoltaic (PV) cell for low illuminance indoor lighting conditions in a material handling and warehousing. Internal parameters were identified using a least squares method.…”
Section: Materials Processing and Energy Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulink Design Optimization Tool (SDO) was used for parameter identification. Masoudinejad et al [63] investigated the use of a serial GB model of a photovoltaic (PV) cell for low illuminance indoor lighting conditions in a material handling and warehousing. Internal parameters were identified using a least squares method.…”
Section: Materials Processing and Energy Materialsmentioning
confidence: 99%
“…"ANN and GA", "LS cost function", "EKF", "non-linear fitting model" [58][59][60] Water treatment estimation and control aeration tank "serial", "parallel", "combined" "ammonium and nitrate concentration", "dissolution rate" "EKF", "ANN" [61][62][63][64] Material processing and energy materials estimation and control "return materials authorization process", "thermotronic system", "photo-voltaic cell" serial temperature "fuzzy membership function", "SDO", "LS" Table 3. GB modeling application in industrial robots and miscellaneous cases.…”
Section: Paper Industrymentioning
confidence: 99%
“…While the two-diode model has been shown to have superior performance in outdoor conditions, conflicting results on its performance have been presented in some of previous studies. For instance, results presented by Masoudinejad et al [9] demonstrated lower performance of the two-diode model when compared to the one-diode model. Moreover, differences in the effects on PV cell performances and losses in indoor lighting conditions have been shown [17], [18].…”
Section: Introductionmentioning
confidence: 96%
“…Photovoltaic (PV) systems under solar lighting have a long history dating back to the 18th century [1]. Long-term research has led to the maturity of this type of energy harvesting with different fields of application [2]: from power production and heating [3] to outer space energy supply [4]. Due to growing enthusiasm for the Internet of Things and Industry 4.0 revolution [5], a new application domain has been opened in recent years to supply embedded devices and cyber-physical systems [6].…”
Section: Introductionmentioning
confidence: 99%
“…Even Standard Testing Condition (STC) AM1.5 is proposed as a part of the IEC60904-3 standard [16], explaining a specific lighting situation to enable comparison of PV modules' performances. In contrast, there are a limited number of works on the indoor performance and analysis of small scale PV modules [2]. In addition to smaller physical size of indoor PV device than a typical solar module, light absorbed by them has a different spectrum [17].…”
Section: Introductionmentioning
confidence: 99%